Outdoor Performance Evaluation of Building Integrated Photovoltaic Thermal (BIPVT) Solar Collector with Spiral Flow Absorber Configurations - Adnan Ibrahim; Sohif Mat; Ahmad Fazlizan Abdullah; Ahmad Fudholi; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
Building Integrated Photovoltaic thermal solar collector (BIPVT) with Spiral flow absorber design is a collector not only used to generate electricity and thermal energy simultaneously but also can be integrated with the roof. Due to it characteristic as a roof, the collector is exposed to the direct sunlight resulting from a higher temperature on it surfaces. The temperature increased will simultaneously decrease it efficiency. An experiment has been conducted outdoor at Universiti Kebangsaan Malaysia to examine and evaluate the efficiency of the collector. Data for the experiment has been collected and gathered from 08:00 to 17:00 respectively. Results from the experiment recorded the best total efficiency of 65.10% (53.64% thermal efficiency and 11.46% electrical efficiency from the PV panel) at mass flow rate of 0.041kg/s and solar radiation of 1148W/m2. The effect of mass flow rates on open circuit voltage (Voc) and the modules short circuit current (Isc) are also presented.